English: English - Synthia Devi, Stefani; Rr. Iramani (Universitas Muhammadiyah Pontianak, 2026)
Teacher performance in international education is often sub-optimal due to administrative burdens and fluctuating motivation. This study examines the effects of training and the work environment on teacher performance, mediated by work motivation at Mawar Sharon Christian School Surabaya. Utilizing a quantitative approach with saturated sampling (N = 110), data collected via questionnaires were analyzed using PLS-SEM. Empirical results prove that both training and the work environment significantly enhance teacher performance, both directly and indirectly through motivation. Consequently, institutions must optimize digital training relevance and workplace quality to foster intrinsic motivation for achieving optimal performance. Keywords: Training; Work Environment; Performance; Motivation